Analysis of Medication Charts of Hospitalized Elderly Patients: A Cross-sectional Study - Sultana, Gouhar; Sai Bharath, Thangella; Goud, Ampelly Nitish; Swetha, Erukala; Nandivardhini, Toku; V, Chandra Sekhar (Indian Journal of Pharmacy Practice)
Objectives: The purpose of conducting the present study was to determine the frequency of PIMs among medication charts of hospitalized elderly patients based on Beer’s Criteria, 2019. Materials and Methods: In a tertiary care hospital, a descriptive, observational cross-sectional study was conducted over the course of six months. The study comprised both male and female in-patients aged 65 years and above. A pre-structured data collection form was used to gather information from the patient case files. Results: A total of 100 prescriptions were included. The most prevalent disease among the elderly was found to be hypertension (15.51%) followed by type 2 diabetes mellitus (14.4%) and sepsis (6.92%). The most commonly prescribed medications among the elderly in the present study were insulin followed by proton-pump inhibitors, atorvastatin, aspirin, and furosemide. A total of 216 potentially inappropriate medications were identified in 87 prescriptions. The use of proton-pump inhibitors was found to be the leading PIM to be avoided followed by insulin. The most common PIM to be used with caution was found to be diuretics followed by aspirin. Conclusion: The study findings show that the frequency of prescribing PIMs is high among hospitalized elderly patients. The use of such medications can be controlled by adhering to the updated Beers criteria.
Keywords: Geriatrics; Polypharmacy; Beer’s criteria; Potentially inappropriate medications; Observational study